Analisis Faktor Indeks Pembangunan Manusia Menggunakan Principal Component Analysis di Provinsi Sulawesi Selatan - Ramadhani, Muta' Alya; Mustawinar, Besse Helmi; Daming, Ahmad Syukur (Pusat Studi Bahasa dan Publikasi Ilmiah, 2025)
This study aims to identify the main factors that influence the Human Development Index in South Sulawesi Province and group variables on the factors formed by the Principal Component Analysis method. The data used in this research is secondary data obtained from the official website of the Central Bureau of Statistics (BPS) of South Sulawesi Province with the unit of observation, namely 24 districts / cities in South Sulawesi Province in 2024. The data was analyzed using the Principal Component Analysis method by reducing the dimensions of large and correlated data into small and uncorrelated dimensions. The results showed that of the nine variables analyzed, two main components were identified that contributed to the formation of the Human Development Index in South Sulawesi Province in 2024, namely the first human quality of life factor with the largest eigenvalue of 3.948 (56.405%), and the second economic and employment factor with an eigenvalue of 1.243 (17.76%). The main factor is interpreted as the quality of human life factor, as it consists of variables most influenced by Expected Years of Schooling (0.875), followed by Average Years of Schooling (0.868), and Life Expectancy (0.772). Meanwhile, the supporting factors were identified as economic and labor factors, which include Labor Force Participation Rate (0.777), Gross Regional Domestic Product (0.735), Per Capita Expenditure (0.726), and Open Unemployment Rate (0.681).